Micro-explosive fragmentation of composite droplets: The effect of components of the aviation fuel; Chemical Engineering Science; Vol. 319 - Antonov D. V. Dmitry Vladimirovich; Dolgikh V. V. Vladimir Viktorovich; Volokitin D. I. Dmitry Ivanovich; Vysokomornaya O. V. Olga Valeryevna (2025, 2025)
Title screen